STUDY KASUS NILAI KEKASARAN PERMUKAAN MATERIAL BAJA S45C PADA PROSES PEMESINAN CNC BUBUT - Riyo Mulyadi; Yudi Oktriadi; Muhammad Rivai (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
In today highly sophisticated manufacturing industry, of course,the best product results are needed. Machining work, especially on CNC turning machining needs to be considered roughness level. The lower the roughness level,  the better the workmanship will be. For this reason it is necessary to pay attention to the parameters used so that the roughness of the product is getting lower. This study aims to determine the best parameters. The machining process is carried out on the MORI SEIKI SL-25B/500 CNC turning and S45C material. Parameters used consist of  feed motion, feed thickness, and spindle speed. The experimental design was based on the taguchimethod with an orthogonal L9(33) matrix and 2 times of replication as a comparison, there was no significant deviation. From the research, the contribution of feeding motion is 49,734%, feeding thickness is 19,239%, and spindle speed is 7,334%. The smallest roughness in the MORI SEIKI SL25B/500 CNC turning machining process was obtained from setting the feed motion 0.2 mm/rev, feeding thickness 1 mm, and spindle speed 2000 rev/minute.